Entrepreneurship Training for University Students Entrepreneurial Programs - Rusnandari Retno Cahyani; Asri Laksmi Riani; Edi Kurniadi; Destina Paningrum (Journal of International Conference Proceedings (JICP), 2018)
This paper’s primary purpose is to emphasize the importance of entrepreneur training (1) Know the potential of human resources and competencies that are owned and can be a provision for entrepreneurial students through training, (2) how important the training for entrepreneurship development, (3) how the training is able to increase the number of entrepreneur. Predict and help provide alternative solutions local and global problems in order to support socioeconomic activities of a community of high competitive based on science and technology. This type of research is qualitative research with data collection using several methods of observation, Interview, Focus Group Discussion, Survey, method refer to documents. Training I with seminars and workshops, attended training II in the form of business clinic coaching and training III that is apprenticeship and practice so as to increase knowledge and develop student business. Keywords: entrepreneurship training, entrepreneurship, entrepreneurial student programs/ESP, culinary business